Effect of swim training on the physical characteristics of competitive adolescent swimmers - Hibberd, E. E.; Laudner, K. G. (The American Journal of Sports Medicine, 2016)
Background: Subacromial space distance and forward head and shoulder posture are common characteristics resulting from swim training. These alterations can cause abnormal scapular kinematics and positioning, potentially increasing compression of structures in the subacromial space and increasing the risk for the development of swimmer`s shoulder. Purpose: To evaluate the effect of the swim training season on subacromial space distance and forward head and forward shoulder posture as well as to determine the relationship between these variables. Study Design: Cohort study; Level of evidence, 2. Methods: Included in the study were 43 competitive adolescent swimmers and 29 nonoverhead adolescent athletes (controls) who were not currently experiencing any shoulder, neck, or back pain that limited their participation in sports activity. All participants were evaluated 3 times: once before the start of the swim training season and then at 2 follow-up sessions 6 and 12 weeks after the initial testing session. At each testing session, each participant completed a physical examination that included evaluation of posture and subacromial space distance. Results: Swimmers had significantly greater decreases in subacromial space distance during the training season compared with nonoverhead athletes. Swimmers also demonstrated significantly greater increases in forward shoulder posture compared with nonoverhead athletes. A significant relationship was noted between changes in forward shoulder posture and changes in subacromial space distance from the baseline testing session to the assessment 6 weeks after baseline assessment. As forward shoulder posture increased, subacromial space significantly decreased. Conclusion: Because of their training load, swimmers experience a decrease in subacromial space distance and an increase in forward shoulder posture over the course of 12 weeks of training, potentially making these athletes more vulnerable to the development of shoulder pain and injury.